Comparative study of vaginal hysterectomy and total abdominal hysterectomy in non-descent uterus - Patel, Rutwa; Kantharia, Preet S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Aim of this study was to compare the outcome of the study of Vaginal Hysterectomy cases (VH) and that of total Abdominal Hysterectomy cases (AH) in non-descent uterus. Methods: The study was carried out at Dhiraj Hospital on the outskirt of Vadodara, Gujarat. For the cases admitted to the Gynaecology unit requiring hysterectomy were randomly selected as 60 cases of VH and 60 cases of AH, during the study period between January 2023 to August 2024. Results: Majority of the patients operated for hysterectomy belonged to 41-50 years of age. Mean age of AH and VH are 44.4 and 43.8 respectively. Most of the patients who underwent hysterectomy are multiparous and weighted mean parity in the AH group is 2.9 and VH Group is 3.2. The most common indications were DUB (38%) of the cases, followed by Adenomyosis (32%), Fibroid Uterus (22%) and PID (8%). Nearly 82% of the patients are delivered vaginally and 13% of these patients has previous caesarean delivery and operated without any major complication. Mean duration of surgery in VH (57 minute) is lower than the AH (75 minutes). Patients of vaginal group ambulated earlier than the abdominal group. Most of the patients discharged between 4-6 days post operatively. Conclusions: Vaginal hysterectomy is a safe, least invasive & most economical route, with lesser complications and should be chosen as the preferred method of hysterectomy, over total abdominal hysterectomy, whenever feasible.